2015
DOI: 10.1017/s0144686x15000525
|View full text |Cite
|
Sign up to set email alerts
|

‘Old but not that old’: Finnish community-dwelling people aged 90+ negotiating their autonomy

Abstract: Autonomy is a pervasive concept in Western lifestyles today. However, people in the fourth age are assumed not to be autonomous but dependent on other people. The data of this study consisted of interviews with Finnish community-dwelling --year-old people. The study aim was to examine how these people see their own autonomy in their everyday lives. The analysis was based on membership categorisation analysis. Our respondents considered their autonomy through three distinct themes. Functional ability was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 57 publications
2
14
0
3
Order By: Relevance
“…Interviewees missed the company of old friends, as well as contact with family members. Pirhonen et al (2016) found that Finnish community-dwelling nonagenarians feared their own transfer into a nursing institution, sometimes even more than dying. Thus, negative representations may isolate residents from their previous friends and same-age peers who are still community-dwellers.…”
Section: Discussionmentioning
confidence: 99%
“…Interviewees missed the company of old friends, as well as contact with family members. Pirhonen et al (2016) found that Finnish community-dwelling nonagenarians feared their own transfer into a nursing institution, sometimes even more than dying. Thus, negative representations may isolate residents from their previous friends and same-age peers who are still community-dwellers.…”
Section: Discussionmentioning
confidence: 99%
“…This side is always in us but it is highlighted in old age. Our youth-oriented culture tends to see old people, as well as people with disabilities, as some kind of others (Pirhonen et al 2015). One probably cannot find a long-term care facility in Finland that has not written the word "individual" in its business idea.…”
Section: Universal Recognitionmentioning
confidence: 99%
“…Based on prior studies it is true that home is the preferred living place for a majority of old people (Jolanki 2009). But this is partly because old people are afraid of institutional long-term care (Pirhonen et al 2015). Old people seem to fear that their autonomy and dignity will be compromised when becoming a resident in long-term care, where "the elderly are dragged from place A to place B" as a 90-year-old lady put it (Pirhonen et al 2015: 9).…”
Section: Equal Recognition In the Fair Distribution Of Care Vs Inequmentioning
confidence: 99%
See 2 more Smart Citations